ACKERMANN, Johann J.H. Inventory of documents - ACKERMANN, Johann J.H. (ARCA, 2018)
Private papers of J.J.H. Ackermann, Public Prosecutor [1950-1957], Medical Representative [1960-1975]
COVERAGE 1957-1960; 1 File; 0.22 metre
Keywords: ACKERMANN, Johann J.H.; South African Bond; South African politics